Leveraging Biomarker Platforms and Systems Biology for Rehabilomics and Biologics Effectiveness Research - Kobeissy, Firas H.; Guingab-Cagmat, Joy D.; Razafsha, Mahdi; O'Steen, Laura; Zhang, Zhiqun; Hayes, Ronald L.; Chiu, Wen-Ta; Wang, Kevin K.W. (PM & R, 2011)
Although traumatic brain injury (TBI) remains a major health problem, with approximately 2 million incidents occurring annually in the United States, no therapeutic agents to treat TBI have been approved by the Food and Drug Administration despite several clinical trials. It is estimated that 3.5 million Americans now have a lifelong condition that might be termed “chronic traumatic brain injury disease.'' Some health care providers categorize TBI as an “event” for which patients require brief periods of rehabilitation with no further treatment. On the contrary, TBI should be seen as a chronic disease process that fits the World Health Organization definition as being a non-reversible pathologic condition requiring special rehabilitation training. Among the major obstacles that contribute to this type of misconception is the absence of brain injury–specific diagnostic biomarker(s) that can indicate and monitor the long-term health status of patients with TBI after use of conventional therapeutics and a rehabilitation process. It is of interest that recent advances in genomics, proteomics, and systems biology have enabled us to use these high throughput–based approaches in developing biomarkers and therapeutic targets in the area of TBI. One aim of this article is to provide an overview that evaluates the current status of TBI biomarker discovery using neuroproteomics/systems biology techniques, along with their clinical utilization. In addition, we discuss the need for strengthening the role of biomarker-based neuroproteomics/systems biology and its potential utility in the field of rehabilitation, which would lead to the establishment of rehabilomics studies, where biomarkers would indicate and predict the long-term efficacy and health status of patients with chronic TBI conditions.